2000
DOI: 10.1161/01.str.31.12.3054
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Transorbital Baboon Model of Reperfused Stroke

Abstract: Background and Purpose-Although pathophysiological studies of focal cerebral ischemia in nonhuman primates can provide important information not obtainable in rodent models, primate experimentation is limited by considerations of cost, availability, effort, and ethics. A reproducible and quantitative model that minimizes the number of animals necessary to detect differences between treatment groups is therefore crucial. Methods-Eight male baboons (weight, 22Ϯ2 kg) underwent left transorbital craniectomy follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 60 publications
3
60
0
Order By: Relevance
“…Another species with less collateralization is Macaca fascicularis, 20,37 while the baboon (Papio anubis) and rhesus (Macaca Mulatta) exhibit collateralization that requires occluding other segments of the MCA. 21,[38][39][40] Studies have previously reported the correlation between functional outcome and size of the infarct. [41][42][43] In the squirrel monkey, focal stroke induced by vascular coagulation using a bipolar electrocoagulator in M1 hand area of the cortex produced motor deficits according to the extent of the injury.…”
Section: Strokementioning
confidence: 99%
“…Another species with less collateralization is Macaca fascicularis, 20,37 while the baboon (Papio anubis) and rhesus (Macaca Mulatta) exhibit collateralization that requires occluding other segments of the MCA. 21,[38][39][40] Studies have previously reported the correlation between functional outcome and size of the infarct. [41][42][43] In the squirrel monkey, focal stroke induced by vascular coagulation using a bipolar electrocoagulator in M1 hand area of the cortex produced motor deficits according to the extent of the injury.…”
Section: Strokementioning
confidence: 99%
“…1 In particular, rodent models have crucial advantages of lower cost, suitability for physiological monitoring, reproducibility of lesion size, and ease of conducting replicate studies. Although Huang et al 2 suggested that the number of animals needed to demonstrate a 50% decrease in infarction volume may be reduced by 41% in their modified transorbital baboon model compared with a previous nonhuman primate stroke model, the coefficient of variation (CV) for infarct volume was still considerably large (62%).…”
mentioning
confidence: 99%
“…29 Baboons were anesthetized with 5 mg/kg IM ketamine (Fort Dodge Animal Health). Two 18-gauge peripheral venous catheters were placed, and intravenous fluid administration of 0.9% normal saline was begun.…”
Section: Anesthesiamentioning
confidence: 99%
“…Animals were subjected to middle cerebral artery territory reperfused stroke as previously described by Huang et al 29 Briefly, they underwent orbital exenteration and removal of the posterior-medial orbital wall under the microscope (Super-Lux 40-2 Illuminator, Zeiss). Dura was opened, and the cerebral arteries were identified.…”
Section: Reperfused Strokementioning
confidence: 99%
See 1 more Smart Citation